Socio-Environmental Factors and Tuberculosis: an Exploratory Spatial Analysis in Peninsular Malaysia - Rauf Abdul Rasam, Abdul; Mohd Shariff, Noresah; F Dony, Jiloris; Misni, Alamah (International Journal of Engineering and Technology, 2018)
Spatial pattern of tuberculosis (TB) describes the environmental variation of the disease. Controlling the disease is not only depends on bio-medical method, but there is also a need to explicitly understand socio-environmental contexts which include the elements of people, space and time. A spatial exploration of local TB dynamic in Malaysia’s perspectives is necessary since earlier studies were limited in addressing these contexts. This paper discusses a general spatial pattern of TB distribution pattern in Peninsular Malaysia for a ten-year period from 2005 to 2014 and its general possible correlation with socio-environmental factors in 2010. Geographical information system (GIS) and correlation analysis are fundamental techniques used to explore the local pattern of TB distribution and the relationship. Data on annual TB cases and state map were collected from the Ministry of Health and the Department of Rural and Country Planning Malaysia respectively. The overall spatial pattern of TB cases has shown increasing trends and concentrating in five states, including Selangor, Johor, WPKL, Kelantan and Kedah, even though there is no specific pattern in the area. This study suggests that the majority of the cases have occurred in the urban states, having high-medium incomes and populous areas.